Mortality rate in patients with nosocomial Acinetobacter meningitis from a Brazilian hospital - Tuon,Felipe Francisco (2010)
BACKGROUND: The mortality rate due to Acinetobacter baumannii nosocomial meningitis (ANM) is high. OBJECTIVE: The aim of this study was to evaluate the factors that have influence over the outcomes in ANM patients. METHODS: A retrospective analysis of 22 cases of ANM was conducted in a hospital with high incidence of multidrug resistance. RESULTS: The mean age of patients was 43 years (21 to 91) and 54.5% were male. All ANM cases occurred within 60 days of admission and the mean duration of illness was of 18.2 days. All cases were associated with previous neurosurgical procedures: elective surgery (27.2%), external shunt (54.4%) and emergency surgery due to trauma (18.1%). Imipenem resistance was observed in 40.9% of cases, but ampicillin/sulbactam resistance was lower (27.2%). The mortality rate of ANM patients was of 72.7%. The only risk factor associated with mortality was inappropriate therapy within five days after CSF collection. All patients who survived the meningitis episode had received appropriate therapy, in contrast to only 69.2% of those who did not survive (OR = 5.15; IC = 0.45-54.01). CONCLUSIONS: The high mortality rate observed in our study suggests the need for aggressive empirical treatment with addition of drugs, including intrathecal therapy, where multi-resistant A. baumannii is endemic